IMPACT MONITORING OF LOW AND HIGH DEXAMETHASONE DOSES ON COVID-19 OUTCOMES IN HODEIDAH, YEMEN: A PHARMACOEPIDEMIOLOGICAL STUDY - MOHAMMED AMOOD AL KAMARANY; ABDULLAH H MAAD; ALI AHMED MOHAJAB; ISRA’A AL-MASRAFI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study aimed to describe the pharmacoepidemiological properties of high and low dexamethasone doses on patients from COVID-19 in Hodeidah, Yemen. Methodology: A randomized clinical trial included 192/323 patients with COVID-19 (28/49 cases in the first wave 2020 and 164/274 cases in the second wave 2021), aged from 3 to 80 years old, confirmed by real time-polymerase chain reaction. All patients were admitted in the isolation department, Center of Tropical Medicine and Infectious Diseases, AL Thawara Public Hospital Authority, Hodeidah, Yemen. 28 patients received high dose of dexamethasone (20–10 mg daily for 10 days) with standard care in the first wave and 164 patients received low dose of dexamethasone (6–8 mg daily for 10 days) in the second wave with standard care. Results: The results showed non-significant differences between the impact of dexamethasone in both waves with different doses of dexamethasone (X2: 1.70; p=0.91). On the other mean, the case fatality rate (CFR) in the first wave with high dose was 10.71% and CFR of the second wave with low dose was 22.29%. While the results showed significant differences between high dose and low dose group with mechanical ventilator “mechanical ventilation (MV)” (X2: 7.10; p=0.0076), the CFR of patients with MV and high dose was 37% and CFR of the second wave with low dose was 77% In addition, all admitted cases had acute respiratory distress syndrome and the onset date of symptom was 2 weeks before hospitalization. Old age, chronic diseases, and co-infection may be contributing factors to effect on dexamethasone efficacy and excess mortality among COVID-19 patients. Conclusion: The study assessed the effectiveness of dexamethasone in high and low dose in treating patients hospitalized with COVID-19 in Hodeidah, Yemen and found difference between mortality and recovery outcomes with high and low dose where the high doses of dexamethasone had good outcome for critical cases with MV.